(untitled) (Analysis in Theory and Applications, 2013)
In this paper, we consider the class of polynomials P(z)=a_nz^n+_ u=μ^na_n- uz^n- u, 1≤ μ≤ n, having all zeros in |z|≤ k, k≤ 1 and thereby present an alternative proof, independent of Laguerre's theorem, of an inequality concerning the polar derivative of a polynomial.